Pengaruh Daya Tarik Iklan Dan Frekuensi Penayangan Di Konvergensi Media Terhadap Minat Beli: (Studi Iklan Traveloka Di Youtube Pada Kalangan Gen Z Di Bandar Lampung) - Florentina Jessica Karnesya; Aripin Ahmad; Nuzul Inas Nabila (Pusat Riset dan Inovasi Nasional, 2024)
Currently, the use of the internet is increasing and information systems are also increasing. This increase in internet use is used to support various aspects, especially business activities. One of the results of the rapid development of the internet is the advertising of products and services via social media. One e-commerce that uses advertising media to offer its products is Traveloka. His research aims to analyze and determine the influence of advertising attractiveness and viewing frequency on buying interest in Traveloka on YouTube among Gen Z in Bandar Lampung. The data used in this study is primary data obtained from respondents through a questionnaire. The population involves people who have seen Traveloka advertisements on YouTube and are interested in purchasing Traveloka application services among Generation Z in Bandar Lampung. The number of samples used was 130 respondents. The results of this research show that the attractiveness of advertising has a positive and significant effect on interest in buying Traveloka products, the frequency of advertising broadcasts has a positive and significant influence on the interest in buying Traveloka products, and the attractiveness of advertising and the frequency of showing simultaneously influence the interest in buying Traveloka products.